Toward multi-species building envelopes: A critical literature review of multi-criteria decision-making for design support. (1st March 2023) - Selvan, Surayyn Uthaya; Saroglou, Soultana Tanya; Joschinski, Jens; Calbi, Mariasole; Vogler, Verena; Barath, Shany; Grobman, Yasha Jacob
Abstract: Rapid urbanization negatively affects the built and biotic environment, necessitating interdisciplinary mitigation strategies. Current nature-based solutions that are integrated into building envelope design have proved to be beneficial. These solutions, however, are primarily anthropocentric and often overlook the potential to support other living organisms, such as animals and microbiota. Thus, a multi-species approach is envisioned to facilitate more holistic envelope-design solutions. While integrating ecological knowledge into architectural design often introduces decision-making complexity, multi-criteria decision-making can support multi-species building envelope design. This paper reviews such decision-making applications in two domains: building envelope design and ecological planning design. Using a systematic literature review methodology to compile relevant publications for full-text analysis, the results show significant disparities between the two domains. This is primarily driven by decision-making applications, the scale of analysis, criteria typology and external decision-maker engagement. However, we identified opportunities to sequentially employ multi-objective optimization and multi-attribute decision-making to mitigate the technical differences and facilitate interdisciplinary collaboration. Finally, we discuss future developments using hybrid multi-criteria decision-making to facilitate better architectural and ecological computer-aided design. Graphical abstract: Image 1 Highlights: The urban fabric lacks holistic strategies to integrate natural ecosystems. Discretized applications of MCDM for multi-species building envelopes are reviewed. Envelope design and ecological analyses have contrasting technical specifications. Decision-making interventions are necessary for holistic multi-species designs. Ecology-integrated architectural design requires a hybrid multi-criteria approach.